Comparision Between Computed Tomography and Ultrasonography in Detection of Urinary Tract Calculi - Paudel, Sharma; Shrestha, Shanta Lall; Mahato, Sahara; Kayastha, Prakash; Suwal, Sundar (Journal of Karnali Academy of Health Sciences, 2020)
Introduction: In the past decade, developments in CT technology have changed the trend of imaging modalities used in the evaluation of urinary system. The present study was undertaken to compare between Computed Tomography (CT) and Ultrasonography (USG) in detection of urinary tract calculi. Methods: This was a cross-sectional and observational study. The study was conducted in Department of Radiology and Imaging of Tribhuvan University Teaching Hospital from June 2017 to September 2017 in 96 patients. Patients who underwent plain CT abdomen (CT KUB) with suspicion of urolithiasis after performing USG were enrolled in the study. Ultrasound and CT findings were compared on the basis of age, gender, clinical complaints, number of stones and their locaton (site of occurrence). Similarly, specificity, sensitivity, positive predictive value and negative predictive value of USG were calculated using CT as gold standard. Results:A total number of 96 patients were studied from June 2017 to September 2017. Among them 56 were males and 40 were females with male to female ratio of 1.4:1. The mean age of male was 34±14.79 years and female was 38±18.74 years.Flank pain was the commonest complaint recorded in 35.41% of patients. On the CT scan, 127 calculi were detected in 96 patients with 31 (32.2%) patients having calculi at multiple sites. Kidney was the most common site of urinary calculi with 77 (60.62)% calculi located in kidneys. Vesico-ureteric junction (VUJ) was the second commonest site with 15 (11.81.%) calculi. Bilateral calculi were seen in 40 (41.66%) patients. Out of the 22 cases with ureteric calculi, USG detected calculi only in 5 cases and the sensitivity of USG in diagnosing ureteric calculi in comparision to CT was 22.72% with 100 % specificity, 100% PPV and 81% NPV. Conclusion: Ultrasound has lower sensitivity for the detection of ureteric calculi. CT helps in precise detection of calculi during initial evaluation which is critical for clinical decision making and patient counselling.